Effects of human opiorphin on food intake and water intake in mice following central administration. (22nd February 2017) - Chen, Yong; Tian, Xiao-Zhu; Bai, Lu; Liu, Ze-Qi; Xiao, Xing-Peng; Liu, Pu; Li, Xiang-Kai
Highlights: Human opiorphin inhibited food intake in fasted and freely feeding mice during the dark period. Human opiorphin increased water intake in fasted and freely feeding mice during the dark period or the light period. The anorexic effect of opiorphin was mainly related to the opioid system and the renin–angiotensin system. The effects of opiorphin on water intake are mediated mainly through renin–angiotensin system via potential protection of endogenous angiotensin from degradation by NEP and APN. Abstract: Human opiorphin plays an important pharmacological functions in rats or mice. The present study was performed to investigate effects and underlying mechanism of central injected opiorphin on food intake and water intake in mice. Intracerebroventricularly (i.c.v.) administered opiorphin (5–20 μg/kg) dose-dependently suppressed food intake in fasted mice, but had no influence on food intake in freely feeding mice. The cumulative food intake was significantly decreased at 60 min after injection of 10 and 20 μg/kg opiorphin and the food intake was significantly reduced during the 20–60 min period after treatment. Non-selected opiate receptor antagonist naloxone could fully block the inhibitory effect induced by opiorphin on cumulative food intake at 60 min in fasted mice, suggesting that the anorexic effect of opiorphin was related to the opioid system. Moreover, the anorexic effect induced by opiorphin in fasted mice was also significantly inhibited by pretreatment with captopril or valsartan, which suggested that endogenous angiotensin may be involved in the response to opiorphin. Interestingly, the effect of opiorphin on water intake was increased in both fasted and freely feeding mice, which was completely blocked by captopril and valsartan. Furthermore, naloxone did not modify the effect of opiorphin on water intake. All together, the food and water intake effects of opiorphin may be due to the protection of the endogenous angiotensin and opioid peptides from degradation by NEP or APN.